Defining Roles for HOX and MEIS1 Genes in Induction of Acute Myeloid Leukemia - Thorsteinsdottir, Unnur (American Society for Microbiology, 2001)
Complex genetic and biochemical interactions between HOX proteins and members of the TALE (i.e., PBX and MEIS) family have been identified in embryonic development, and some of these interactions also appear to be important for leukemic transformation. We have previously shown that HOXA9 collaborates with MEIS1 in the induction of acute myeloid leukemia (AML). In this report, we demonstrate that HOXB3, which is highly divergent from HOXA9, also genetically interacts with MEIS1, but not with PBX1, in generating AML. In addition, we show that the HOXA9 and HOXB3 genes play key roles in establishing all the main characteristics of the leukemias, while MEIS1 functions only to accelerate the onset of the leukemic transformation. Contrasting the reported functional similarities between PREP1 and MEIS1, such as PBX nuclear retention, we also show that PREP1 overexpression is incapable of accelerating the HOXA9-induced AML, suggesting that MEIS1 function in transformation must entail more than PBX nuclear localization. Collectively, these data demonstrate that MEIS1 is a common leukemic collaborator with two structurally and functionally divergent HOX genes and that, in this collaboration, the HOX gene defines the identity of the leukemia.